Crocin lessens desipramine-induced phospholipidosis biomarker levels via targeting oxidative stress- related PI3K/Akt/mTOR signaling pathways in the rat liver.: Crocin modulating effect in phospholipidosis - Ahmed El-Sheikh, Amal; A. Mahmoud, Heba; Ali El-Kordy, Eman; M. Abdelsattar, Amal; H. Rizk , Fatma; Mahmoud El-Sharaby, Radwa; S. Mashal, Shimaa; A. EL Saadany, Amira; H. Shalaby , Rania; M. Elshamy, Amira; Safwat El-deeb, Omnia; Raafat Ibrahim, Rowida; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim Crocin is a pharmacologically active chemical found in the spice saffron from Crocus sativus L. It possesses antioxidant and anti-radical properties that can minimize the hepatic phospholipidosis triggered using the tricyclic antidepressant desipramine. The aim of this study was to examine the effect of crocin on desipramine-induced hepatic phospholipidosis targeting the oxidative stress-related PI3K/Akt/mTOR signaling pathways. Methods: Forty adult male rats were divided into 4 groups (n =10): control group, a group receiving intraperitoneal (IP) crocin (50 mg/kg/day), a group receiving IP desipramine (10 mg/kg/day), and a group receiving both IP crocin and desipramine. Results: After 3 weeks of treatment, the combined treatment group showed diminished desipramine-induced hepatic phospholipidosis, along with significant reductions in total oxidant status (TOS) , the levels of inflammatory markers including interleukin 6 (IL6) and tumor necrosis factor α (TNF-α) and apoptotic markers including caspase3 and Bcl2 (B-cell lymphoma 2) while other markers including total antioxidant capacity (TAC), superoxide dismutase (SOD), phosphoinositide 3-kinases (PI3K), and mammalian target of rapamycin (mTOR) were increased. The gene expression of lysosomal enzymes including ELOVL6, SCD1 and HMGR was notably downregulated, while AP1S1 was upregulated in the combined treatment group compared to the desipramine group. No ultrastructural signs of hepatic phospholipidosis, in the form of multilamellar bodies, were apparent in the combined treatment group. Conclusions: These data collectively suggest that crocin has a protective effect against desipramine-induced phospholipidosis. (www.actabiomedica.it)